2018
DOI: 10.1038/s41598-017-19092-1
|View full text |Cite
|
Sign up to set email alerts
|

Iron-induced calcification in human aortic vascular smooth muscle cells through interleukin-24 (IL-24), with/without TNF-alpha

Abstract: In CKD patients, arteriosclerotic lesions, including calcification, can occur in vascular smooth muscle cells in a process called Moenckeberg’s medial arteriosclerosis. Iron overload induces several complications, including the acceleration of arteriosclerosis. However, the relationship between Moenckeberg’s arteriosclerosis in vascular smooth muscle cells and iron accumulation has remained unknown. We tested the accelerated effect of iron on calcification in cultured human aortic vascular smooth muscle cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 38 publications
0
20
1
Order By: Relevance
“…As in the early stages of atheroma, lipid accumulation in the fibrosa can promote the development of angiogenesis within the valves, a process always associated with aortic valve diseases. In this context, microcalcifications develop in the fibrosa and could cause neovascularization tears and hemorrhages, which accelerate the calcification process [94], because hemoglobin and its derivatives (heme, ferrous iron, free radicals and NF-kB activation) promote the release of exosomes and the osteoblastic differentiation of valvular interstitial cells [95] as well as of SMCs in the arterial wall [96]. Therefore, there is a vicious circle between calcifications and RBC/iron which promotes exponential development of both valvular and vascular calcifications in association with CV risk factors: aging, tobacco, dyslipidemia, etc.…”
Section: Rbcs and Vascular Calcificationsmentioning
confidence: 99%
“…As in the early stages of atheroma, lipid accumulation in the fibrosa can promote the development of angiogenesis within the valves, a process always associated with aortic valve diseases. In this context, microcalcifications develop in the fibrosa and could cause neovascularization tears and hemorrhages, which accelerate the calcification process [94], because hemoglobin and its derivatives (heme, ferrous iron, free radicals and NF-kB activation) promote the release of exosomes and the osteoblastic differentiation of valvular interstitial cells [95] as well as of SMCs in the arterial wall [96]. Therefore, there is a vicious circle between calcifications and RBC/iron which promotes exponential development of both valvular and vascular calcifications in association with CV risk factors: aging, tobacco, dyslipidemia, etc.…”
Section: Rbcs and Vascular Calcificationsmentioning
confidence: 99%
“…Atherosclerosis caused by oxidative damage, and evidenced by increased circulating mononuclear superoxide production and vascular cell adhesion molecule-1 (VCAM-1) and triggered by NADPH oxidase (NOx) and NF-kB activation in CKD patients, is associated with IV iron administration [67,68,69,70]. Against this evidence, some studies on the role of iron in CKD pathogenesis showed contradictory results [71]. Iron deposition in the liver of both humans [72] and rats [73] did not develop into cirrhosis, possibly because of iron sequestration into innocuous ferritin L and H subunits.…”
Section: Iron Oxidative Stress and Anemiamentioning
confidence: 99%
“…Another mechanism that was proposed as a process that prevents iron overload in tissues such as the liver is the secretion of iron-loaded ferritin [74], possibly by an iron-regulated exocytosis efflux process [75] into blood circulation. However, other evidence revealed that high doses of iron were associated with high mortality due to iron-induced oxidative stress [68,71].…”
Section: Iron Oxidative Stress and Anemiamentioning
confidence: 99%
“…In this regard, some reports have indicated that increased iron in vitro enhances calcification of both endothelial (Nanami et al, 2005) and smooth muscle cells (Kawada et al, 2018) through inflammation and oxidative stress. In addition, it has been proposed that aortic calcification may be causally linked to arterial stiffness and increased PWV in humans (Guo et al, 2017;Sekikawa et al, 2012;Tsao et al, 2014) and a rat model of vascular disease (Ng et al, 2011).…”
Section: Discussionmentioning
confidence: 99%